1998
DOI: 10.3748/wjg.v4.i6.511
|View full text |Cite
|
Sign up to set email alerts
|

Segmental transcatheter arterial embolization for primary hepatocellular carcinoma

Abstract: AIM:To evaluate the therapeutic effects of segmental transcatheter arterial embolization for primary hepatocellular carcinoma, and to recognize the menifestation and clinical value of lipiodol overflow into portal veins surrounding the tumors.METHODS:A total of 50 cases of nonresectable primary hepatocellular carcinoma underwent segmental transcatheter arterial embolization. Two methods of superselective segmental catheterization were used, one was the method of wire-guiding, and the other the technic of co-ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Since TACE was introduced as a palliative treatment in patients with unresectable HCC, it has become one of the most common forms of interventional therapies [11,31] . TACE with iodized oil has been shown to result in regression of HCC and reduction of systemic toxicity, thus improving the therapeutic effects [21,32,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TACE was introduced as a palliative treatment in patients with unresectable HCC, it has become one of the most common forms of interventional therapies [11,31] . TACE with iodized oil has been shown to result in regression of HCC and reduction of systemic toxicity, thus improving the therapeutic effects [21,32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection, liver transplantation and cryosurgery are regarded as potentially curative treatment for HCC [3][4][5] , but most patients are not suitable candidates [6][7][8][9] . Thus, the local interventional therapy of liver tumor has been rapidly evolving currently, which includes transarterial chemoembolization (TACE), percutaneous ethanol injection (PEI), radiofrequency ablation (RFA), laser-induced thermotherapy (LITT) and microwave coagulation therapy (MCT) [10][11][12][13][14][15][16][17][18][19] . TACE is one of the most common forms of interventional therapies and seems most effective against encapsulated small HCCs without extracapsular invasion, whereas in large HCCs, viable residual tumor cells remain and the tumor frequently recurs [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection, liver transplantation, and cryosurgery are regarded as potentially curative treatment for HCC, but most patients are not suitable candidates [3]. Currently the local interventional therapy of liver tumor has been rapidly evolving, which includes transarterial chemoembolization (TACE), percutaneous ethanol injection (PEI), radiofrequency ablation, laser-induced thermotherapy, and microwave coagulation therapy [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that TACE improves survival compared with best supportive care in meta-analyses of randomized trials [6,7] and in two individual clinical trials [8,9] . Nowadays TACE is often performed by selective catheterization of the hepatic segmental arteries nourishing the HCC lesions, to limit as much as possible the injury to the surrounding non tumorous liver as reported in previous studies [10][11][12] . However, although selective TACE is currently widely used, to our knowledge there are no reported extensive data from large series on both short and long term effects of this treatment on liver function.…”
Section: Introductionmentioning
confidence: 99%